The Relationship Between Seismic and Aseismic Slip on the Philippine Fault on Leyte Island: Bayesian Modeling of Fault Slip and Geothermal Subsidence. Issue 12 (29th November 2020) - Dianala, John Dale B.; Jolivet, Romain; Thomas, Marion Y.; Fukushima, Yo; Parsons, Barry; Walker, Richard
Abstract: Delineating seismic and aseismic slip on faults allows the exploration of the complex relationship between these different modes of slip. Further, quantifying them helps in the assessment of seismogenic potential. We present a distributed slip model of the rate of aseismic slip along the Leyte island section of the Philippine Fault and make comparisons with the extent of seismic slip from the latest significant earthquakes in July 2017. We derived both coseismic and aseismic slip distributions from kinematic inversions of synthetic aperture radar interferometric (InSAR) observations using a probabilistic (Bayesian) framework. Velocity maps from stacking and time series analysis of ALOS interferograms spanning 4 years (2007–2011) show a step change in ground deformation right on the fault. Inverting for slip at depth reveals along‐strike variations of aseismic slip rate over ∼100 km. Aseismic slip on the surface reaches rates of more than 3 cm/yr, equivalent to the long‐term slip rate (3.3 ± 0.2 cm/yr). Over the same period, a 20‐km segment in Tongonan appears to be locked. This segment ruptured in M w 6.5 and M w 5.8 earthquakes on 6 and 10 July 2017, respectively, as constrained by Sentinel‐1 and ALOS‐2 InSAR data. Seismic slip appears to be restricted within the Tongonan segment, with up to 152 ± 21 cm of left‐lateral displacement. The slip budget and complementarity between the extents of interseismic and coseismic slip suggest that a seismogenic asperity exists in Tongonan. The presence of active hydrothermal systems and rate‐strengthening materials provide physical conditions that can promote aseismic slip. Plain Language Summary: In July 2017, the Philippine Fault on Leyte island produced a damaging earthquake that was unexpected. Previous studies that tracked the movement of the Earth's crust have suggested that the fault in Leyte does not accumulate strain, and hence stress, as the fault primarily slides stably and slowly. This is in contrast to earthquake‐generating faults that go on a cycle of building up stress for a long period of time, due to the crust staying stuck (or locked) on the fault, and then releasing the stored stress as an earthquake. With analysis of high‐resolution satellite radar, we now show that while 100 km of the fault indeed appears to be moving slowly and gradually, a 20‐km‐long portion in the middle of the fault appears to be locked. Our observations and models of the July 2017 earthquake confirm that this same section of the fault alone moved then. The geometry of the fault, the abundance of fluids, and the presence of specific types of minerals may all play a role on how the fault behaves. This work is the first of its kind on the Philippine Fault, highlighting the importance of exploring relatively less well studied faults and their physical properties. Key Points: We present the first probabilistic model of interseismic aseismic slip throughout seismogenic depth along 100 km of the Philippine Fault Joint inversion for anthropogenic subsidence and fault deformation reveals downdip locking from the surface on a 20‐km section in Tongonan Extent of seismic rupture of the July 2017 magnitude 6.5 and 5.8 earthquakes correlates with geometric complexity and lack of slip deficit